Regulation of Factor VIII Expression and Activity by von Willebrand Factor - Kaufman, Randal J.; Pipe, Steven W. (Thrombosis and Haemostasis, 1999)
Hemostasis requires a cascade of proteolytic reactions that occurs on the surfaces of damaged or activated cells, such as platelets, white blood cells, and endothelial cells. Initial damage to a blood vessel results in platelet adhesion to the subendothelium mediated by von Willebrand factor (vWF). Subsequently, platelet activation and aggregation occur. Protease complexes assemble on the surface of activated cells and are converted sequentially to their proteolytically active forms to result in a localized burst of thrombin generation and the conversion of soluble fibrinogen to insoluble fibrin. Activation of the extrinsic coagulation pathway occurs to form a factor VIIa—tissue factor complex on activated or damaged endothelial cells. In turn, factor VIIa activates the intrinsic pathway of blood coagulation by activating factor IXa, which in turn interacts with activated factor VIIIa, in the presence of calcium and negatively-charged phospholipids, to convert factor X to factor Xa. Factor Xa then acts with its cofactor factor Va, in the presence of calcium and negatively-charged phospholipids, to convert prothrombin to thrombin. Initial factor Xa and thrombin generation feeds back to activate cofactors VIII and V. Activation of these cofactors in the intrinsic pathway serves to amplify thrombin generation. The importance of this cascade in hemostasis is evident from the characterization of individuals who are defective in proteins that function in this cascade. The most common of these disorders, a deficiency of factor VIII that results in hemophilia A, was documented more than 1,700 years ago in the Talmud.1The genetics of hemophilia A was described in the early 1800s, and transfusion of whole blood was shown to successfully treat a hemophilia A-associated bleeding episode by 1840.2,3 Although the presence of factor VIII in plasma was demonstrated in 19114 and its role in hemostasis was described in 1937,5 a detailed biochemical and structural characterization of factor VIII was achieved only within the last 20 years. Prior to 1980, the relationship between hemophilia A and von Willebrand’s disease generated a great deal of confusion because the autosomally-inherited von Willebrand’s disease is associated with some degree of factor VIII deficiency, although hemophilia is an X-linked disease. In addition, early preparations of antihemophilia factor not only corrected the clotting time of hemophilic plasma, but also restored platelet adhesion and aggregation defects in the plasma of patients with von Willebrand’s disease. It is now appreciated that factor VIII and vWF are two separate proteins that exist as a complex in plasma. They are under separate genetic control, have distinct biochemical and immunological properties, and have unique and essential physiological functions (Table 1). Factor VIII is the X-linked gene product that accelerates the factor IXa-mediated activation of factor X by four orders of magnitude. vWF is an autosomal gene product that is essential for platelet adhesion to the subendothelium and for ristocetin-induced platelet aggregation. In addition, vWF plays a critical role in the regulation of factor VIII activity by 1) stabilizing factor VIII on secretion from the cell;6,7 2) requiring the survival of factor VIII in plasma,8,9 3) protecting factor VIII from activation by factor Xa and inactivation by activated protein C;10,11 and 4) preventing factor VIII from binding to phospholipids and activated platelets.3,12It is likely that vWF mediates its inhibitory properties on factor VIII by preventing factor VIII from binding to phospholipids, an interaction required for both factor Xa- and APC-mediated cleavage of factor VIII. Because vWF and factor VIII are found in plasma as a complex and vWF stabilizes factor VIII and regulates its activity, the activities of these two proteins are intimately intertwined.